Prospective Study of Intestinal Parasites in Children Hospitalized in the Pediatric Department at the Hospital in El Eldrissi (Kenitra City - Morocco) - Hafida, Hammour; Khadija, El Kharrim; Driss, Belghyti (European Scientific Journal, ESJ, 2017)
The aim of this study is to determine the epidemiology and prevalence of intestinal parasites in children hospitalized in the pediatric ward at the hospital El Eldrissi Kenitra during the period 2011 from the month February to May. During the study period a prevalence of 49% was recorded among the whole sample studied. The male is the most parasitized with 63%. The mean age was 6.5 ± 0.39 year. Child aged 4 to 10 years are most affected with a frequency of 57%. The majority of parasitised patients were from rural areas (64%). The results of the parasitological analysis showed predominance of protozoa (90.6%) compared with Helminths (9.4%).